2012
DOI: 10.1177/0956797612446349
|View full text |Cite
|
Sign up to set email alerts
|

Don’t Judge a Book by Its Cover, Revisited

Abstract: Research has documented a robust stereotype regarding personality attributes related to physical attractiveness (the "what is beautiful is good" stereotype). But do physically attractive women indeed possess particularly attractive inner attributes? Studying traits and values, we investigated two complementary questions: how perceived attractiveness relates to perceived personality, and how it relates to actual personality. First, 118 women reported their traits and values and were videotaped reading the weath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…As guiding principles, values drive behaviors that allow the attainment of important goals and prevent people from taking actions that undermine their attainment (e.g., Roccas & Sagiv, 2010;Segal-Caspi, Roccas, & Sagiv, 2012). In a systematic study of value-behavior relationships, Bardi and Schwartz (2003) demonstrated that value-expressive behaviors form a circular structure that resembles the structure of personal values.…”
Section: Values and Behaviormentioning
confidence: 99%
“…As guiding principles, values drive behaviors that allow the attainment of important goals and prevent people from taking actions that undermine their attainment (e.g., Roccas & Sagiv, 2010;Segal-Caspi, Roccas, & Sagiv, 2012). In a systematic study of value-behavior relationships, Bardi and Schwartz (2003) demonstrated that value-expressive behaviors form a circular structure that resembles the structure of personal values.…”
Section: Values and Behaviormentioning
confidence: 99%
“…A substantial amount of research exists on the halo effect, and it is evident that the halo effect affects people's judgments in a variety of ways. Studies have shown that, because of the halo effect, people are often unfairly attributed with qualities that they may not actually possess (Eagly, Ashmore, Makhijani, & Longo, 1991;Feingold, 1992;Segal-Caspi, Roccas, & Sagiv, 2012). The study conducted by Bak and Köln (2010) provided the impetus for the present study.…”
Section: Psi Chi Journal Of Psychological Researchmentioning
confidence: 90%
“…A substantial amount of research exists on the halo effect, and it is evident that the halo effect affects people's judgments in a variety of ways. Studies have shown that, because of the halo effect, people are often unfairly attributed with qualities that they may not actually possess (Eagly, Ashmore, Makhijani, & Longo, 1991;Feingold, 1992;Segal-Caspi, Roccas, & Sagiv, 2012). The study conducted by Bak and Köln (2010) provided the impetus for the present study.…”
Section: Psi Chi Journal Of Psychological Researchmentioning
confidence: 94%